2016
DOI: 10.1111/aos.13098
|View full text |Cite
|
Sign up to set email alerts
|

Use of new imaging in detecting and monitoring ocular manifestations of the mucopolysaccharidoses

Abstract: The aim of this review is to summate the eye involvement in patients with mucopolysaccharidoses (MPS) using current ocular imaging techniques, their advantages and disadvantages and how they may aid diagnosis, management and monitoring. We critically reviewed the current literature surrounding MPS and recent imaging technology as well as histology. Primary searches of PubMed and Web of Science were performed. We reviewed all papers on the topic published and summarized the findings of each medical device as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Subjective assessment of corneal clouding may be subject to inter-and intraobserver variability, and VA may fluctuate in patients with MPS due to variable lighting conditions, patients' concentration and co-operation. The Iris camera has been previously validated to provide an objective measure of corneal clouding in patients with MPS (Aslam et al 2012;Javed et al 2016), and the Pentacam Densitometry Program has also been shown to provide an objective measure of corneal clouding in patients with MPS with moderate-to-severe corneal clouding (Elflein et al 2013). However, the Pentacam digital imaging system requires patient co-operation, and many patients may not be able to tolerate the assessment due to age or intellectual and physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective assessment of corneal clouding may be subject to inter-and intraobserver variability, and VA may fluctuate in patients with MPS due to variable lighting conditions, patients' concentration and co-operation. The Iris camera has been previously validated to provide an objective measure of corneal clouding in patients with MPS (Aslam et al 2012;Javed et al 2016), and the Pentacam Densitometry Program has also been shown to provide an objective measure of corneal clouding in patients with MPS with moderate-to-severe corneal clouding (Elflein et al 2013). However, the Pentacam digital imaging system requires patient co-operation, and many patients may not be able to tolerate the assessment due to age or intellectual and physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Iris Camera (similar to the security tool used in airports) is used to allow the grading of corneal clouding; this examination shows high repeatability [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of ocular imaging modalities in MPS has previously been reviewed by our group12 and were thought to be useful in objectively assessing the ocular phenotype in MPS.…”
Section: Introductionmentioning
confidence: 99%